2012
DOI: 10.1038/cr.2012.135
|View full text |Cite
|
Sign up to set email alerts
|

A functional variant in the cystathionine β-synthase gene promoter significantly reduces congenital heart disease susceptibility in a Han Chinese population

Abstract: Homocysteine is an independent risk factor for various cardiovascular diseases. There are two ways to remove homocysteine from embryonic cardiac cells: remethylation to form methionine or transsulfuration to form cysteine. Cystathionine β-synthase (CBS) catalyzes the first step of homocysteine transsulfuration as a rate-limiting enzyme. In this study, we identified a functional variant −4673C>G (rs2850144) in the CBS gene promoter region that significantly reduces the susceptibility to congenital heart disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…Studies have found that the expression of fetal CBS is concentrated in the neural and cardiac tissues, supporting a hypothesis of its involvement in embryo cardiac development (Quere et al 1999; Robert et al 2003). In particular, a recent study in Han Chinese population identified a functional variant (rs2850144) in CBS that is significantly associated with the genetic susceptibility to CHDs (Zhao et al 2012). This SNP (rs2850144, BP: 43370045) was not genotyped in our study, but it is located approximately 5.5 kb from the identified haplotype block (BP 43354960–43364494).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the expression of fetal CBS is concentrated in the neural and cardiac tissues, supporting a hypothesis of its involvement in embryo cardiac development (Quere et al 1999; Robert et al 2003). In particular, a recent study in Han Chinese population identified a functional variant (rs2850144) in CBS that is significantly associated with the genetic susceptibility to CHDs (Zhao et al 2012). This SNP (rs2850144, BP: 43370045) was not genotyped in our study, but it is located approximately 5.5 kb from the identified haplotype block (BP 43354960–43364494).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies showed that one-carbon metabolism gene polymorphisms were associated with the balance of one-carbon metabolism and the genome-wide DNA methylation levels in breast cancer and colorectal cancer14151617. Moreover, our previous study identified several noncoding variants within one-carbon metabolism genes were able to impair the one-carbon metabolism balance and were associated with increased risk of birth defect181920. However, whether those noncoding variants contributed to the occurrence of cancer remains unknown.…”
mentioning
confidence: 98%
“…Furthermore, to the best of our knowledge, there are few studies of the possible correlation between genetic variations in the noncoding region of one-carbon metabolism genes and PCa risk have been published. The aim of the present study was to investigate the contribution of functional non-coding variants to the risk of PCa in a large-scale hospital-based case-control study, including MTR rs28372871, MTR rs1131450, MTRR rs326119 and CBS rs2850144181920. Moreover, we assessed the effects of other extensively reported polymorphisms of genes in the one-carbon metabolism pathway, including MTR rs1805087 and MTRR rs18013944631, on the risk of PCa in our cohort.…”
mentioning
confidence: 99%
“…Two new studies examined possible roles of common polymorphisms in the methionine synthase reductase ( MTRR ) and cystationine β–synthase ( CBS) genes in more than 2300 CHD cases and a like number of controls, both groups being Han Chinese [18,19]. For MTRR , the minor c.56+781 A>C intronic allele engendered a 1.36-fold per allele increase in CHD risk such that individuals with the CC genotype had a 1.8-fold risk [18].…”
Section: Methyl Metabolismmentioning
confidence: 99%
“…For CBS , a-4673C>G allele in the promoter reduced the risk of CHD such that child with the CG genotype had a 15% and those with the GG genotype had a 40% reduction in CHD risk compared to children with the reference CC genotype [19]. No epistatic relationship to the MTRR c.56+781 C allele was detected.…”
Section: Methyl Metabolismmentioning
confidence: 99%